Issues emerging from universal test and treat (UTT) intervention trials - (:unkn) unknown (My University, 2013)
Universal repeat testing and early antiretroviral treatment (UTT) strategies to reduce onward sexual transmission are major social, as well as biomedical interventions. Several UTT trials are underway or being prepared. This paper discusses some emerging issues arguing extensive social science within UTT trials needs complementary enquiry to guide public health and operational decisions beyond the trials themselves.The issues fall under three broad headings:Social and behavioural consequences of large numbers of people knowing their HIV-status and potentially beginning treatment early. Will the impacts on sexual behaviour, disclosure and stigma all be positive? Harmful?Normative changes at individual and community levels. What normative changes occur in communities exposed to prolonged, intense research around unspoken or socially taboo subjects? Does seeing more healthy people attending clinics alter community perceptions of disease and care? Can salient positive changes be identified and replicated?Operational and ethical implications of transforming research interventions into routine care. Who should lead? Requirements for sustainability. Impacts of institutions ‘knowing’ about individuals’ HIV status and care uptake, especially in contexts of criminalisation and marginalised or vulnerable populations?UTT strategies have potentially great social consequences that need to be explored alongside the actual trials, to guide and inform future decisions and policy.
Keywords: African Research